PAW21 Rewarding visual cues increase dopamine neurotransmission in Parkinson's patients with impulse control disorders: a PET study. Issue 11 (22nd October 2010) - Wu, K; O'Sullian, S; Politis, M; Bose, S; Lees, A; Piccini, P
Abstract : Background: Current evidence connects impulse control disorders (ICDs) to dopaminergic replacement therapy used for the treatment of Parkinson's disease (PD). Common ICDs include hypersexuality, pathological gambling, compulsive shopping and binge eating. The underlying neuropathology is thought to be due to sensitisation of the dopaminergic system in the striatum and related neurocircuitry. Aim: To investigate the effect of rewarding visual cues on dopamine neurotransmission in PD patients with ICDs. Methods: Ten ICD PD patients and five PD controls underwent two randomised positron emission tomography (PET) scans with 11C-raclopride (RAC) after a medication challenge with levodopa while observing neutral or rewarding (gambling, sex, food and money) images. Scans were analysed using region-of-interest approach. Results: The ICD PD group showed a significant decrease of RAC binding in ventral striatum (p=0.001) and caudate nucleus (p=0.015) in response to rewarding images (compared to neutral images), where in PD controls there was no difference. Discussion: Our PET results suggest a significant increase in the release of endogenous dopamine in ventral striatum and caudate nucleus in PD patients with ICDs and further support the role of dopaminergic pathways in mediating ICDs. The response to visual stimuli alone may be of relevance to new treatment strategies.